Pelatihan Mengenal dan Mengoptimalkan Prompt GPT untuk Pembelajaran Digital di SMK PAB 8 Sampali - Alfina, Ommi; Syahputri, Nita; Lahilote, Abqoriy Hisan; Rustam, Muhammad Taufiq; Safii, M. (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The training program titled "Introduction and Optimization of GPT Prompts for Digital Learning at SMK PAB 8 Sampali" was conducted as an effort to enhance digital literacy and technological skills among teachers and students. In the era of Education 4.0, artificial intelligence (AI) technology, particularly Generative Pre-trained Transformer (GPT), holds great potential to support teaching and learning processes, including generating exam questions, summarizing materials, and planning lessons. This training aimed to provide basic understanding of GPT concepts and practical skills in crafting effective prompts for various educational purposes. The implementation method employed hands-on practice and real-life case studies within the SMK environment. The results showed an improvement in teachers' and students' abilities to utilize AI technologies, as well as increased awareness of the importance of ethical and creative use of technology in digital education. Through this training, SMK PAB 8 Sampali is expected to become a pioneer in the application of AI in vocational secondary schools in Medan.